Seasonal Analysis of River Flow at Sang-i-Naweshta Station - Reshteen, Sediqullah (Journal of Natural Sciences – Kabul University, 2020)
The flow of rivers constitutes a negligible portion of all available water on Earth, yet the seasonal variations in river flow are of great importance to human activities. As rainfall increases, water flows into the Earth's surface, forming rivers. Precipitation, air temperature, and evapotranspiration are among the climatic factors that influence river flow. Rivers are a primary source of water consumption, and understanding their flow is essential for better management and analysis. Plans for designing water systems or hydrologic systems are largely based on monthly, seasonal, and annual hydrological data of river flows. Seasonal analysis of river flow is especially important due to its impact on water supply, water balance, agricultural activities, and other uses.